(untitled) (Revista Brasileira de Iniciação Científica, 2023)
Considering the matter of inquiry aspects and autonomy for the individuals’ scientific education, we carried out a state-of-the-art study whose objective was to analyze the experimental activities, reported in master’s dissertations and doctoral theses in Physics Teaching, defended in brazilian post degree research-programs between 2001 and 2019. Based on searches in the CEDOC-UNICAMP thesis and dissertation database, we selected 218 studies and identified 992 experiments in them. The analysis points to a low inquiry feature developed in the activities, with 62% of the experiments having closed-quality scripts, making it difficult for students to act autonomously